PENGARUH PELATIHAN TERHADAP PRODUKTIVITAS PEGAWAI PADA KANTOR SEKRETARIAT DAERAH KOTA TANGERANG SELATAN - Lilis Suryani (Universitas Pamulang, 2017)
ABSTRACT This study aims to determine whether there is influence of training on the productivity of employees at the Secretariat office of South Tangerang city. Population of the study was an employee at the Regional Secretariat of South Tangerang, amounting to 80 people and they are sample of the research. Employee development can be implemented in the form of implementation of the training for employee is one of the ways to create human quality resources with the goals and objectives of the Regional Secretariat of South Tangerang city. The method used of the research is observation and questionnaires. Observation methods used to collect the data by direct observation in the field over all studied. Interviews are used to obtain data about the historical development of management and other types of training provided by the Regional Secretariat using the guidelines questionnaire to collect the data by dividing the list of statements to the respondent. From the calculation by using the Pearson correlation coefficient formula that there is a positive correlation between training and productivity of employees, which amounted to r = 0.715 and determination coefficient of 51.12% productivity is influenced by training. While the remaining 48.88% influenced by other factors such as internal and external environment, skills, office management and so on.